Platelet-Derived Growth Factor (PDGF)/PDGF Receptors (PDGFR) Axis as Target for Antitumor and Antiangiogenic Therapy - Anca Maria Cimpean; Marius Raica (MDPI AG, 2010)
Angiogenesis in normal and pathological conditions is a multi-step process governed by positive and negative endogenous regulators. Many growth factors are involved in different steps of angiogenesis, like vascular endothelial growth factors (VEGF), fibroblast growth factor (FGF)-2 or platelet-derived growth factors (PDGF). From these, VEGF and FGF-2 were extensively investigated and it was shown that they significantly contribute to the induction and progression of angiogenesis. A lot of evidence has been accumulated in last 10 years that supports the contribution of PDGF/PDGFR axis in developing angiogenesis in both normal and tumoral conditions. The crucial role of PDGF-B and PDGFR-β in angiogenesis has been demonstrated by gene targeting experiments, and their expression correlates with increased vascularity and maturation of the vascular wall. PDGF and their receptors were identified in a large variety of human tumor cells. In experimental models it was shown that inhibition of PDGF reduces interstitial fluid pressure in tumors and enhances the effect of chemotherapy. PDGFR have been involved in the cardiovascular development and their loss leads to a disruption in yolk sac blood vessels development. PDGFRβ expression by pericytes is necessary for their recruitment and integration in the wall of tumor vessels. Endothelial cells of tumor-associated blood vessels can express PDGFR. Based on these data, it was suggested the potential benefit of targeting PDGFR in the treatment of solid tumors. The molecular mechanisms of PDGF/PDGFR-mediated angiogenesis are not fully understood, but it was shown that tyrosine kinase inhibitors reduce tumor growth and angiogenesis in experimental xenograft models, and recent data demonstrated their efficacy in chemoresistant tumors. The in vivo effects of PDGFR inhibitors are more complex, based on the cross-talk with other angiogenic factors. In this review, we summarize data regarding the mechanisms and significance of PDGF/PDGFR expression in normal conditions and tumors, focusing on this axis as a potential target for antitumor and antiangiogenic therapy.